Effectiveness of the Mini Nutritional Assessment (MNA) in Evaluating Malnutrition in Patients with Chronic Obstructive Pulmonary Disease (COPD): A Systematic Review - Erisca Carolina; Agung Waluyo; Denissa Faradita (GLOBAL HEALTH SCIENCE GROUP, 2025)
Patients with Chronic Obstructive Pulmonary Disease (COPD) are at high risk of weight loss. This weight loss can exacerbate malnutrition, which is closely associated with worsened lung function, increased hospitalization rates, decreased physical activity tolerance, reduced quality of life, and higher mortality. The Mini Nutritional Assessment (MNA) is a widely used questionnaire that provides clear information regarding nutritional status and helps assess malnutrition in patients. Objective to evaluate the effectiveness of the Mini Nutritional Assessment (MNA) in assessing nutritional status and predicting malnutrition in COPD patients. This article is written using a systematic review method, with a search strategy conducted across four databases, yielding a total of 871 articles. These articles were then screened based on inclusion and exclusion criteria, resulting in 7 articles from 2014-2024. The 7 selected articles were subjected to critical appraisal using the JBI Critical Appraisal Checklist. The review of the articles generally indicates that the MNA intervention is effective in assessing malnutrition in COPD patients. The MNA can be optimally used to predict malnutrition in COPD patients, particularly among the elderly.